(untitled) - Lampert, Lincoln Maximilian (New York, 1975)
This book presents reliable information, in a non-technical manner, on the composition, nutritive value, manufacture, chemistry, and bacteriology of milk and dairy products. The book introduces the reader to the broad aspects of the dairy industry and the possibilities of bringing in new techniques. Visit us at www.chemical-publishing.com
Keywords: Milk,Dairy products,Sữa